PHARMACOLOGICAL MANAGEMENT OF ORAL LESIONS IN ADENOID CYSTIC CARCINOMA PATIENTS UNDERGOING RADIOTHERAPY - ROSA, DESI ELVHIRA; ADHISTY, THEODORA; DEWI, TENNY SETIANI (International Journal of Applied Pharmaceutics, 2022)
Objective: This case report aimed to describe the pharmacological management of oral lesions in adenoid cystic submental carcinoma patients undergoing radiotherapy. Methods: A 48 y old female undergoing radiotherapy complained of difficulty eating, swallowing, and speaking due to severe pain in her oral cavity for three weeks. Intra-oral examination revealed painful yellowish-white plaques that could not be scrapped on the tongue, maxillary and mandibular anterior gingiva, left and right buccal mucosa, and palate, diagnosed with oral candidiasis. We also found multiple shallow ulcers on the left buccal mucosa and upper labial mucosa that can be seen as oral mucositis. Results: The patient was given nystatin oral suspension for oral candidiasis, benzydamine hydrochloride for the complaint of pain when swallowing, and saline for promoting wound healing and keeping the oral mucosa moist. These lesions healed in a week and she could eat solid food without pain. Conclusion: Appropriate pharmacological management of oral lesions in a patient undergoing radiotherapy provides significant healing to better quality of life.